The integrated hydrologic model intercomparison project, IH‐MIP2: A second set of benchmark results to diagnose integrated hydrology and feedbacks. Issue 1 (25th January 2017) - Kollet, Stefan; Sulis, Mauro; Maxwell, Reed M.; Paniconi, Claudio; Putti, Mario; Bertoldi, Giacomo; Coon, Ethan T.; Cordano, Emanuele; Endrizzi, Stefano; Kikinzon, Evgeny; Mouche, Emmanuel; Mügler, Claude; et al.
Abstract: Emphasizing the physical intricacies of integrated hydrology and feedbacks in simulating connected, variably saturated groundwater‐surface water systems, the Integrated Hydrologic Model Intercomparison Project initiated a second phase (IH‐MIP2), increasing the complexity of the benchmarks of the first phase. The models that took part in the intercomparison were ATS, Cast3M, CATHY, GEOtop, HydroGeoSphere, MIKE‐SHE, and ParFlow. IH‐MIP2 benchmarks included a tilted v‐catchment with 3‐D subsurface; a superslab case expanding the slab case of the first phase with an additional horizontal subsurface heterogeneity; and the Borden field rainfall‐runoff experiment. The analyses encompassed time series of saturated, unsaturated, and ponded storages, as well as discharge. Vertical cross sections and profiles were also inspected in the superslab and Borden benchmarks. An analysis of agreement was performed including systematic and unsystematic deviations between the different models. Results show generally good agreement between the different models, which lends confidence in the fundamental physical and numerical implementation of the governing equations in the different models. Differences can be attributed to the varying level of detail in the mathematical and numerical representation or in the parameterization of physical processes, in particular with regard to ponded storage and friction slope in the calculation of overland flow. These differences may become important for specific applications such as detailed inundation modeling or when strong inhomogeneities are present in the simulation domain. Key Points: Seven hydrologic models were intercompared using three benchmarks of increasing complexity Models showed good agreement with respect to various hydrologic responses (storage, discharge, and soil moisture values) Different discretizations of the digital elevation model had stronger influence than mathematical model formulation